2005
DOI: 10.1007/s00428-005-1213-7
|View full text |Cite
|
Sign up to set email alerts
|

A case of mucoepidermoid carcinoma with melanin pigmentation manifested in the palate

Abstract: This paper describes the first documented case of mucoepidermoid carcinoma (MEC) with melanin pigmentation manifested in the palate. Histopathological sections showed a neoplasm composed of epidermoid, mucous-producing and intermediate cells. Numerous large cells contained dark pigmented materials. Fontana Masson staining revealed dendritic melanocytes and melanin granules. HMB-45, Melan A and S-100 protein were all positive for melanocytes. Histopathological examination was not typical for malignant melanoma;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Pigmented salivary gland tumors are unusual. A review of English literature revealed several melanin-pigmented salivary gland tumors, including 18 Wartin's tumor [8], 5 mucoepidermoid carcinoma (MEC) [9][10][11][12][13], 2 adenoid cystic carcinoma (AdCC) [14,15] and 1 pleomorphic adenoma (PA) [16]. Melanocyte-like cells in the tumor stroma were observed in all cases, whereas some cases also presented pigment granules within tumor cells [10-12, 15, 16] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Pigmented salivary gland tumors are unusual. A review of English literature revealed several melanin-pigmented salivary gland tumors, including 18 Wartin's tumor [8], 5 mucoepidermoid carcinoma (MEC) [9][10][11][12][13], 2 adenoid cystic carcinoma (AdCC) [14,15] and 1 pleomorphic adenoma (PA) [16]. Melanocyte-like cells in the tumor stroma were observed in all cases, whereas some cases also presented pigment granules within tumor cells [10-12, 15, 16] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The other cases were of mucoepidermoid tumors, where the pigment-producing cells were proved to be melanocytes [1][2][3]8]. More recently, a case of pleomorphic adenoma with melanin pigment has been described [7].…”
Section: Discussionmentioning
confidence: 96%
“…Only 5 tumors of salivary gland origin containing numerous melanocytes and melanin pigment in the parenchyma and/or stroma have been documented (15)(16)(17)(18)(19). Moreover, a review of the literature has yielded no convincing examples of pre-existing melanocytes in the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…The second case was in a Caucasian who had been suffering from well-differentiated mucoepidermoid carcinoma of buccal minor salivary gland origin, reported in 1985 (16). Sekine et al (17) reported a third pigmented mucoepidermoid carcinoma of the palatal minor salivary gland origin in a Japanese patient. Clinical behavior of carcinoma is not related to existence of melanocytes; although one of the reported cases (15) was associated with lymph node metastasis, the others including the present were non-metastatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation